2022
DOI: 10.3390/s23010192
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometers in Our Pocket: Does Smartphone Accelerometer Technology Provide Accurate Data?

Abstract: This study evaluates accelerometer performance of three new state of the art smartphones and focuses on accuracy. The motivating research question was whether accelerator accuracy obtained with these off-the-shelf modern smartphone accelerometers was or was not statistically different from that of a gold-standard reference system. We predicted that the accuracy of the three modern smartphone accelerometers in human movement data acquisition do not differ from that of the Vicon MX motion capture system. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
(51 reference statements)
0
18
0
Order By: Relevance
“…First, participants used a range of personal smartphone devices, and this may introduce potential errors due to data sampling from variations in smartphone devices, operating software platforms, and motion sensors. Grouios et al [36] compared acceleration data from three smartphones, including iPhone 12 Pro Max, Samsung Galaxy S21 Ultra, and Huawei P Smart, and concluded that the mean acceleration data were not statistically different between the devices. This result was similar to other research studies [37,38] that compared accelerometer sensor performance between commercially available smartphones, suggesting that modern smartphone accelerometers can be used for measuring human movement and be employed in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…First, participants used a range of personal smartphone devices, and this may introduce potential errors due to data sampling from variations in smartphone devices, operating software platforms, and motion sensors. Grouios et al [36] compared acceleration data from three smartphones, including iPhone 12 Pro Max, Samsung Galaxy S21 Ultra, and Huawei P Smart, and concluded that the mean acceleration data were not statistically different between the devices. This result was similar to other research studies [37,38] that compared accelerometer sensor performance between commercially available smartphones, suggesting that modern smartphone accelerometers can be used for measuring human movement and be employed in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…HD: This study focused on demonstrating the feasibility of gait analysis using smartphones and was thus completed in a relatively small cohort of healthy young adults. 10 14 We chose young, healthy adults as the experimental cohort based on their ease of cooperation and ability to perform standardized gait tests in experimental settings with complex equipment configurations; they can provide controllable and reliable gait patterns at different walking speeds. This study recruited 30 young, healthy adults (16 males and 14 females; age 26.400 ± 1.545 years; height 172.333 ± 8.314 cm; weight 65.370 ± 11.357 kg).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 2 , two smartphones (iPhone 13) were attached to the waist and thigh, while an inertial measurement unit (N200, WHEELTEC, China; sampling rate: 100 Hz) was fixed at the shank as the reference device for validation purposes. Each participant was asked to walk six gait cycles at self-selected 10 , 12 14 , 17 low, normal, and high speeds along a flat corridor. Normal speed walking is defined as walking at a comfortable speed, high-speed walking is preferred, and as fast as possible, and low-speed walking is defined as walking cautiously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10]. The prevalent use of accelerometers in HAR may be explained by the low cost and small size of the device as standalone sensors, and additionally, their low energy consumption and high feature performance, as demonstrated in modern smartphones, further contribute to their widespread adoption [11,12].…”
Section: Introductionmentioning
confidence: 99%